Wielodziałowy model wzrostu społeczno-gospodarczego - Nieduszyński, Mieczysław (Wydział Prawa i Administracji UAM, 1976)
The matter of analysis is a problem of the dynamic programming. The idea of a complex analysis of development of the Polish economy in 1970 - 1972, namely a multi-sector econometric model of dynamic equlibrium, is presented. The time horizon of the model has been divided into three périodes of time, each one year long, called stages. The whole Polish economy has been divided into seven sectors, namely: 1) industry, 2) building and housing construction, 3) agriculture, 4) forestry, 5) transport and communication, 6) commerce and 7) all a rest of production. There was elaborated a multistage and multi-sector mathematical model in which are considered the effects of three basic factors of growth, namely: the amount of capital invested, the degree of modernization of the production apparatus and the "human capital", on individual components of the national income in various stages, in all the horizon and in each sectors. The "human capital" is a potential of education, science, technical progress, health care, sport, tourism, rest, culture and arts accumulated over a certain period of time as a result of the activity of a society in the nonmaterial sphere of production. The subject matter of the paper is the optimization of financial — production flows in stages and sectors of the national economy using a multi — stage transportation problem which, from the standpoint of the calculation technique, is reduced to the scheme of a classical transportation problem. From the analysis of the optimum solution it results that in the years 1970 - 1972 there existed additional possibilities of a better utilization of some productive resources and capacities in all sectors of the Polish economy. There particularly existed possibilities of raising the consumption and investment outlays by ca 92 bilion zł and possibilities of decreasing the inventories by ca 69 bilion zł.
The Multi-Sector Model of a Social and Economic Development